2012
DOI: 10.1111/j.1532-950x.2012.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Functional Outcome of Tibial Plateau Leveling Osteotomy Versus Extracapsular Repair in a Heterogeneous Population of Dogs

Abstract: Dogs achieved normal limb loading faster after TPLO than ECR. TPLO resulted in operated limb function that was indistinguishable from the control population by 1 year postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 49 publications
(82 reference statements)
2
76
0
6
Order By: Relevance
“…Consequently, surgical procedure could also influence time to contralateral CR. Functional outcome at 12 months after treatment with tibial plateau leveling osteotomy (TPLO) is superior to treatment with a lateral fabellar suture [16], [17], and meta-analysis of surgical treatments suggests that evidence most strongly supports the ability of TPLO to return dogs to normal function [18].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, surgical procedure could also influence time to contralateral CR. Functional outcome at 12 months after treatment with tibial plateau leveling osteotomy (TPLO) is superior to treatment with a lateral fabellar suture [16], [17], and meta-analysis of surgical treatments suggests that evidence most strongly supports the ability of TPLO to return dogs to normal function [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have shown surgical stabilization to be effective in managing cranial cruciate ligament insufficiency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). While there are numerous options for surgical management, surgery is not always an option.…”
Section: Introductionmentioning
confidence: 99%
“…Two frequently utilised surgical procedures for stabilisation of a CCL‐deficient stifle include tibial plateau levelling osteotomy (TPLO) and lateral fabellotibial suture (LFS) (Nelson et al . ). TPLO is purported to impart functional stifle stability during the stance phase of the gait cycle by eliminating cranial tibial thrust (CrTT) but it has been shown to incompletely eliminate internal tibial rotation (Slocum & Slocum , , Warzee et al .…”
Section: Introductionmentioning
confidence: 99%